Land cadastre development in Ukraine: issues to be addressed - Popov, Andriy; Попов, Андрій Сергійович (Vilnius : 2019, 2019)
EN: Cadastral information is a key component for many land use functions and a core to the effective land markets, land use and sustainable development. These applications require up-to-date, reliable and complete data. This paper focuses on one aspect of land cadastre – identification of the objects of the cadastre. The characteristics and development of the existing cadastral system are discussed. We follow an empirical approach and propose an overview how and in what form the objects of state land cadastre are identified and registered in Ukraine. The paper analyses the problems associated with the plurality of the land cadastre objects. It is proposed to remove the registration numbers of the state land cadastre objects and new cadastral numbers of the land parcel from the legislation and return the legalization of the old cadastral number of the land parcel. The paper also underlines the necessity to consider the land parcel as a single object of the state land cadastre. Finally, it is proposed that the cadastral number of restrictions in the use of the land parcel will be an immense advantage in land registration and in visualisation the restrictions on the public cadastral map of Ukraine.
Keywords: land cadastre; land parcel; land registration; cadastral number; registration number; object; restriction